Phylogenetic Perspectives on Catarrhine Talo‐Crural Joint Phenotypic Plasticity. Issue 11 (7th June 2019) - Simons, Evan A.; Turley, Kevin; Frost, Stephen R.
ABSTRACT: Previous investigations of the primate talo‐crural joint (TCJ; specifically on the talus and distal tibia) have demonstrated that substrate preference significantly influences morphology, but this association is not necessarily found in subadults. This has been interpreted as the result of a plastic, behaviorally induced response of bone due to substrate use. In this investigation, we use geometric morphometric and phylogenetic comparative methods to investigate ontogenetic phenotypic plasticity in the catarrhine TCJ. Osteological specimens from four African hominoid and four cercopithecid species, divided into subadult and adult developmental stages based on molar eruption, formed the study group. We tested for phylogenetic signal in the shape of both the talar and tibial articular surfaces, at both developmental stages. We then used phylomorphospaces to examine the evolution of shape differences at each developmental stage for each element, and to determine if substrate usage is associated with shape in this phylogenetic context. A significant phylogenetic signal was found for both articular surfaces in subadults, but not adults. In phylomorphospace, both talar and tibial articular morphologies show an association with substrate preference in adults, but not in subadults. Our results provide confirmation of the significant effect of habitual substrate usage and the consequences of bone remodeling during ontogeny on the shape and presentation of the TCJ. These results also suggest caution when using adult talo‐tibial shapes to evaluate phylogenetic relationships as TCJ morphology can be considered as a palimpsest, with substrate usage overwriting phylogenetic information in adult specimens. Anat Rec, 302:1977–1984, 2019. © 2019 American Association for Anatomy